An Exploratory Study to Find Unique Marketing Strategies of China's Rapid Growing Multi-National Fast-Food Chains - RUITENG, XUE; GHOSH, ABHIJIT (International Journal of Multidisciplinary Research and Studies, 2023)
In China, the fast-food business has expanded dramatically during the last several decades. Consumers in China are becoming pickier about the foods they buy, reflecting the country's expanding level of consumption. The emphasis of this research is on the moderating effect of gender on the relationships between customer satisfaction, loyalty, & happiness. Five hundred Chinese respondents who have eaten at Western fast-food restaurants (KFC, McDonald's, etc.) filled out an online survey to compile the data. There was a favorable correlation between consumer satisfaction and the quality of the perceived pricing, food, service, & physical setting. Customers' evaluations of a restaurant's quality on a variety of parameters might be heavily influenced by how much they feel they are paid. Moreover, client joy and contentment may inspire devoted patronage. The connection between contentment and dedication is mediated by happiness. Yet, researchers found that there is a small gender gap in how evaluate the value of a meal based on the cost, as well as how satisfied they are with the quality of the service they received. Future research will benefit from this study since it will improve our comprehension of management and theoretical viewpoints.